As Peculiaridades das Ocupações Irregulares no Distrito Federal - Blanco, Karoline Cunha (2018)
Considering the peculiarity presented by the illegal occupation in the territory of the Federal District was conducted an overview of the concepts assigned to that occupation format and developed a brief history that seeks to identify the origins of the problem. The study results in a reflection on the dimensions of the problem of illegal occupation in the territory of the Federal District, as well as the importance attached to the name front the search for a solution to the problems presented. Seeks an overview of the situation of the Federal District on the rampant growth of illegal occupation aimed subsidies for the development of studies to investigate possible solutions or mitigation strategies for the problems arising from illegal occupation.